Effect of vitamin D supplementation on COVID-19 outcomes: an umbrella review of systematic reviews - Petakh, Pavlo; Kamyshna, Iryna; Halabitska, Iryna; Kamyshnyi, Oleksandr (Frontiers in Nutrition, 2025)
BackgroundVitamin D is suggested as a supportive therapy to reduce the severity of COVID-19 due to its immunomodulatory and anti-inflammatory effects. However, its effect on critical outcomes, such as ICU admissions and mortality, shows significant variation across randomized clinical trials and meta-analyses.ObjectivesTo summarize the influence of vitamin D supplementation on ICU admissions and mortality among COVID-19 patients.MethodsOverall, 21 eligible studies were retrieved using a comprehensive search from Scopus, PubMed, and Web of Science. A citation matrix was developed, revealing a Corrected Covered Area (CCA) of 0.54, indicating moderate overlap. Fixed-effects models were applied to data with low heterogeneity (ICU admissions: Q = 10.87, p = 0.33), while random-effects models were used for mortality outcomes (Q = 27.23, p = 0.006). Pooled odds ratios (OR) with 95% confidence intervals (CI) quantified the overall effects.ResultsVitamin D supplementation was associated with a significant 38% reduction in ICU admissions (OR = 0.62; 95% CI: 0.54–0.71) and a 33% reduction in mortality risk (OR = 0.67; 95% CI: 0.56–0.79). The benefit was pronounced in vitamin D-deficient populations, although heterogeneity in mortality outcomes highlighted variability across studies.ConclusionWhile these findings suggest that vitamin D supplementation may help reduce ICU admissions and mortality among COVID-19 patients—particularly in those with vitamin D deficiency—the results should be interpreted with caution. The observed variability and potential confounding factors underscore the need for further large-scale, randomized controlled trials with standardized dosing protocols before definitive clinical recommendations can be made.